2022
DOI: 10.1111/cea.14203
|View full text |Cite
|
Sign up to set email alerts
|

Elicitors and phenotypes of adult patients with proven IgE‐mediated food allergy and non‐immune‐mediated food hypersensitivity to food additives

Abstract: Background Food allergy is a growing health concern with a prevalence of 2%–3% in the adult population in Europe. Non‐immune‐mediated food hypersensitivities, which include reactions after ingestion of food additives, affect 1% of adults and may resemble IgE‐induced allergic reactions without identifiable immunologic sensitization. A double‐blind placebo‐controlled food challenge (DBPCFC) is the gold standard for the diagnosis of any food hypersensitivity. Objective We analysed a large group of adult patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Two parameters appear to emerge from this pilot study, beyond a mere interest as biomarkers, as potential contributors in the pathogenic pathways involved in long/post-COVID: (i) HERV-W ENV, known to be a potent TLR4 agonist in immunopathogenic as well as in neurotoxic processes ( 48 50 ), and (ii) IgE antibodies known to be strong effectors of immunoallergic conditions as well as anti-parasite humoral responses ( 51 , 52 ). Thus, the present study strongly suggests focussing further studies on their potential role in certain forms and/or symptoms of post-COVID syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Two parameters appear to emerge from this pilot study, beyond a mere interest as biomarkers, as potential contributors in the pathogenic pathways involved in long/post-COVID: (i) HERV-W ENV, known to be a potent TLR4 agonist in immunopathogenic as well as in neurotoxic processes ( 48 50 ), and (ii) IgE antibodies known to be strong effectors of immunoallergic conditions as well as anti-parasite humoral responses ( 51 , 52 ). Thus, the present study strongly suggests focussing further studies on their potential role in certain forms and/or symptoms of post-COVID syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the results from previous studies, higher levels of total IgE at baseline in participants were associated with increased intake of food proteins, such as egg, milk, peanut, and tree nuts ( 36 ). Because of the characteristics of UPFs ( 37 ), in patients with a higher intake of UPFs, it is difficult for the body to produce an allergic reaction ( 38 , 39 ). On the other hand, it was reported that IgE sensitization and food hypersensitivity declined with increasing age ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…The consumption of increasing amounts of dietary sugars and fast food is to be factored with studies showing that there is ingestion of 7–8 kg per person per year of synthetic chemical additives including preservatives, acidity regulators, colorants and emulsifiers ( 90 ). These additives have been linked to allergic outcomes, most likely via their alteration of microbiome composition and function ( 91 , 92 ). The Western diet has less omega 3 fatty acids ( 93 ) and dietary fiber ( 94 ), both of which have been suggested to further contribute to risk of allergic disease ( 95 , 96 ).…”
Section: The Western Diet and The Rise Of Food Allergymentioning
confidence: 99%